Using Scammers’ Data to Estimate the Impact and Importance of Preventing Repeat Mail Fraud Victimization - Langton, Lynn (The British journal of criminology, 2025)
This study examines the frequency and cost of repeat mail fraud victimization in the United States using longitudinal data from a unique source: records from four scam enterprises that operated over a nearly 20-year period. Findings show that most mail fraud victims experience repeat victimization and a small percentage account for most of the losses. Sixty-two per cent of victims responded to more than one mail solicitation. Chronic victims, who responded more than 20 times, comprised 8.8 per cent of the sample and lost $1,771, on average. Findings suggest the need for early intervention to prevent repeat and chronic victimization, thereby reducing the harm for victims. Limitations and implications for future research are discussed.